Workshop Guru Pembelajaran Berbasis STEAM - Seruni; Indah Lestari; Nurul Hikmah (CV. Multi Kreasi Media, 2025)
Community Partnership Program (PKM) activities were carried out at SMP Negeri 210 Jakarta as a partner in the implementation of the program. The participants involved in this activity were all teaching staff at SMP Negeri 210. The purpose of this activity is to: a) Improve the knowledge and skills of partners in designing STEAM-based learning; b) Deepen partners' understanding of STEAM learning design. Some of the challenges faced by partners include: a) low literacy about STEAM knowledge, b) lack of understanding of the importance and benefits of implementing STEAM in the learning process, c) limited training or workshops that discuss innovations in learning, especially related to STEAM. The methods used include preparation, implementation, and evaluation between implementers and partners, as well as the organization of workshops on the implementation of STEAM. This method was applied to a partner group of 40 people. The results achieved from this activity are: 1) Skill improvement and change of partner perspective in STEAM learning; 2) Partners are able to design STEAM-based learning.